A new electrochemical sensing platform for Cr(III) determination based on nano-structured Cr(III)-imprinted polymer-modified carbon composite electrode. (1st September 2017) - Alizadeh, Taher; Rafiei, Faride; Hamidi, Negin; Ganjali, Mohamad Reza
Graphical abstract: Highlights: The nano-structured Cr(III)-imprinted polymer was synthesized using itaconci acid. The imprinted polymer was used as the recognition element of a carbon paste electrode. An open circuit pre-concentration approach was used for Cr(III) accumulation on CPE. The electrochemical signal was obtained via oxidation of up-tacken Cr(III) to Cr(VI). LOD and sensitivity of the electrode were 17.6 nM and 4.25 A mol −1 L, respectively Abstract: A carbon composite electrode (CCE) impregnated with nano-structured Cr(III)-imprinted polymer (IP-CCE) was introduced as a novel sensing platform for Cr(III) measurement. The nanoparticles of Cr(III)-imprinted polymers were synthesized using itaconic acid and ethylene glycol dimethacrylate, as complexing monomer and cross-linker, respectively. For analysis purpose, the electrode was incubated into the Cr(III) solution for a definite time and then differential pulse voltammetry technique was applied for the relevant signal recording. The Oxidative differential pulse voltammetry response of Cr(III) obtained using the IP-modified electrode was significantly higher than that recorded by either CCE or the CCE included with the non-imprinted polymer (NIP). Various factors, known to affect the response behavior of the IP-CCE, were investigated and optimized. The sensor exhibited distinct linear response ranges of 0.1 − 10 μmol L −1 with the sensitivity of 4.25 A mol −1 L. The lower detection limit of the sensor was calculated to be 17.6 nmol L −1 (S/N = 3). The sensor was applied successfully for the determination of Cr(III) in water and urine real samples.